Comparative Estimation of Tracheostomy Time and Procedures in Patients with Multiple Organ Dysfunction after Cardiosurgical Interventions - L. S. Barbarash; Ye. V Grigoryev; G. P. Plotnikov; B. L. Hayes; V. Yu. Kheraskov (Общая реаниматология, 2010)
Objective: to comparatively evaluate the efficiency of tracheostomy by various methods in different artificial ventilation periods in patients with multiple organ dysfunction after cardiosurgical intervention. Subjects and methods. In the first stage, the patients in whom tracheostomy was performed in a classical surgical manner (a control group; n=15) not earlier than 7 days after arterial ventilation (AV) were compared. A study group comprised 19 patients in whom tracheostomy was carried out on days 3—4 after AV. In the second stage of the study, tracheostomy was made not later than 4 days following AV: by the puncture-dilatation method in study group 2 (n=28) and by the classical surgical procedure in control group 2 (n=49). Results. The time and procedures of an intervention were found to have an impact on the bacteriological profile of a patient, the duration of switch to spontaneous respiration, and the tracheobronchial tree. The advantages and disadvantages of the puncture-dilatation technique of tracheostomy were noted from the standpoint of hemodynamics, gas transport, possible complications, and long-term Results. Conclusion. Early tracheostomy caused a reduction in the number of infectious complications of the tracheobronchial tree, early decannulation with switch to spontaneous breathing. The puncture-dilatation procedure of tracheostomy is characterized by the minimum hypoxic period at cannula installation and ensures prompt healing in the absence of purulent complications. The classical surgical tracheostomy remains to be the method of choice during massive anticoagulant therapy. The accumulation of long-term results should be continued. Key words: tracheostomy, multiple organ dysfunction, cardiac surgery.